Impact of Board Gender Diversity and Derivatives Use on Firm Risk - Dwi Dewisri Kinasih; Nuraini Desty Nurmasari; Joni Prayogi (Journal of Economics, Business, and Accountancy Ventura, 2023)
In the wake of the recent global pandemic, COVID-19, companies need to maintain performance and manage firm risk. Companies should understand what can affect the firm's risk. This paper investigates the impact of board diversity and derivatives use on firm risk. The sample consists of 35 Indonesian LQ45 listed on the Indonesia Stock Exchange with an observation period of 2016–2020. The company's risk is proxied by the standard deviation of stock returns. This study uses a panel data regression model, namely fixed effect regression and random effect regression. The results of this study indicate that female board directorship is negatively associated with firm risk. It shows the significant role of female board directors in the company's board. Meanwhile, the use of derivatives has no significant effect on the firm risk. These results impact the development of literature that examines the influence of board diversity and the use of derivatives for hedging in Indonesia so that companies can determine company policies to reduce risk.